Philosophical Perspective of the Community Counseling Services to Facilitate Adolescents’ Development in Indonesia: A Systematic Review - Lestari, Rizqi; Purwanta, Edi; Rukiyati, Rukiyati (Universitas Mathla'ul Anwar Banten, 2025)
Guidance and counseling have ontological, epistemological, and axiological foundations that are the basis for the implementation of services both in schools and outside schools. As one of the services in guidance and counseling, community counse1ling services cannot be separated from the underlying philosophical perspective, especially tp facilitate adolescents' development. This research aims to analyze the philosophical perspective of community counselling implementation to facilitate the development of adolescents in Indonesia. The research method used is a systematic literature review. The data collection technique was carried out by searching for articles on Google scholar using the keywords